Students’ Experiences with Web-Based Alcohol Prevention: A Qualitative Evaluation of AlcoholEdu - Nygaard, Peter (J Drug Educ, 2012)
AIM: To provide more in-depth information about students’ experiences with AlcoholEdu and in particular to assess if students perceive that the course gives them tools to better control their drinking-related behavior. METHODS: Focus group interviews with freshmen at three California universities. FINDINGS: 1) The course provides so much information that everyone can find some of it relevant; 2) participants prefer information presented in ways they can identify with; 3) participants report problems with surveys in the program pointing to redundancy and length; and 4) participants did not expect the course to impact their behavior relating to alcohol. CONCLUSION: AlcoholEdu provides valuable information for freshmen in college about how to avoid problems with alcohol. However, the course could have much more impact if closer to college reality.